Some representative species of the tribe Holochlorini (Orthoptera: Tettigoniidae: Phaneropterinae) and the description of two new species from India - Swaminathan, R.; Nagar, Rajendra (Zootaxa, 2016)
In the present paper two new species of the genus Holochlora (Phaneropterinae: Holochlorini) have been described viz., Holochlora umranensis sp. nov., collected from Meghalaya, the North-eastern province, India (Ri bhoi 90°55’15 to 91°16’ latitude and 25°40’ to 25°21’ longitude, 993 MSL) and Holochlora alsigarhensis sp. nov., collected from Southern-western, Rajasthan, (Udaipur N 24 34’17 to E 73 41’ 30’’ and Latitude 24.5713, Longitude 73.6915, 582 MSL), as additions to the previously known species of the genus that were earlier collected from the southern parts of India. Among these, four species are being reported for the first time from India including: H. brevifissa, H. fruhstorferi, H. japonica and Rectimarginalis profunda Liu & Kang. The key morphological characters of the head, pronotum, tenth abdominal tergite, subgenital plate, cerci, titillator and the ovipositor have been illustrated with suitable line drawings to distinguish the known, reported and new species, along with a key to the genera and species.